(untitled) (Mustansiria Dental Journal, 2004)
Tumour thickness measurement was evaluated in relation to clinical nodal status on 26 patients with oral squamous cell carcinoma. The measurement estimated on Haematoxylene and Eosin stained microscopic sections of the resection specimen of each case by using a micro - occulmeter on illuminated viewer. The thickness considered the distance between surfaces epithelium from which the invasion started to the deepest invading front. Analysis of clinical data showed that 14 of the cases had palpable lymph nodes, whereas 12 cases had no palpable nodes. It was found that the mean tumour thickness in group with palpable nodes was 9.5 mm. whereas the mean tumour thickness in group with no palpable nodes was 4.5 mm. This difference, statistically, using t-test was highly significant (p < 0.004). It si concluded, therefore, that, tumour thickness as a single structural parameter can help ni the prediction of cervical lymph nodes involvement ni patients with oral squamous cell carcinoma. Thus, an additional method of treatment can be chose following local resection of the tumour